Pertumbuhan dan Hasil Kacang Tanah (Arachis hypogaea L.) Pada Beberapa Jenis Pupuk Kotoran Hewan dan Gandasil D - Elsa S. Nainggolan; Veronica L. Tuhumena; Inna M. Rumainum; Wasgito Purnomo (Agrotek, 2023)
This study used a Factorial Completely Randomized Design (CRD). The first factor was planting media (M) which consisted of three categories, namely: topsoil (M0), mixed soil and goat manure with a ratio of 2:1 (M1), soil and chicken manure with a ratio 2:1 (M2). The second factor was foliar fertilizer (P), which consisted of no foliar fertilizer (P0) and application of gandasil D fertilizer (P1). The results showed that the M0 treatment had a significant effect on the weight of the pods and the fresh weight of the plant, but did not have a significant effect on the plant height, the number of branches and the flowering time. The application of gandasil D has no significant effect on all observed variables. The combination of media type and gandasil D had a significant effect on plant height at 3 WAP in the M2P1 treatment, the number of pods in the M2P1 treatment, the weight of the pods planted in the M0P1, M0P0 treatments, and the fresh pod weight in the M0P0, M2P1, M1P0 treatments, but had no significant effect on plant height, number of branches and flowering time. In the observed variables of pod weight and fresh pod weight, the application of animal manure gave a good response to the availability of nutrients that can be absorbed by plants.